The Comparison Between Topical 5-Fluorouracil and Trichloroacetic Acid in The Treatment of External Genital Condyloma Accuminatum - Karaca, Kenan; Aka, Nurettin; Köse, Gültekin; Kumru, Pınar; Sayharman, Sema (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: To investigate the effects of fluorouracil cream and 80% trichloroacetic acid solution in the treatment of condyloma accuminatum. STUDY DESIGN: 35 non-pregnant women with a diagnosis of vulvar condyloma accuminatum were randomly assigned to two groups as,5-fluorouracil group (n=17) and trichloroacetic acid group (n=18). All patients were examined after 7 days and after 6 months and were evaluated with respect to the effectiveness, side effects and recurrence rates. RESULTS AND CONCLUSION : Both methods were found to be effective in the treatment of external condyloma accuminatum. When the two groups were evaluated with respect to cost per patient, the average cost was detected to be 2 USD for the trichloroacetic acid group and 20 USD for the 5-fluorouracil group.